2022
DOI: 10.3389/fphar.2022.991052
|View full text |Cite
|
Sign up to set email alerts
|

Link of sorafenib resistance with the tumor microenvironment in hepatocellular carcinoma: Mechanistic insights

Abstract: Sorafenib, a multi-kinase inhibitor with antiangiogenic, antiproliferative, and proapoptotic properties, is the first-line treatment for patients with late-stage hepatocellular carcinoma (HCC). However, the therapeutic effect remains limited due to sorafenib resistance. Only about 30% of HCC patients respond well to the treatment, and the resistance almost inevitably happens within 6 months. Thus, it is critical to elucidate the underlying mechanisms and identify effective approaches to improve the therapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 206 publications
0
11
0
Order By: Relevance
“…21 However, newer therapies based primarily on Sor appear to induce a modest increase in HCC patient survival. 22 However, significant drug resistance to Sor reduces the therapeutic effect of patients. 23 At the same time, over 50% of patients experience severe clinical side effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 However, newer therapies based primarily on Sor appear to induce a modest increase in HCC patient survival. 22 However, significant drug resistance to Sor reduces the therapeutic effect of patients. 23 At the same time, over 50% of patients experience severe clinical side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Only patients who cannot be treated by resection are candidates for drug therapy 21 . However, newer therapies based primarily on Sor appear to induce a modest increase in HCC patient survival 22 . However, significant drug resistance to Sor reduces the therapeutic effect of patients 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, several studies reported that sorafenib inhibits EMT in a variety of experimental settings [21][22][23]. Moreover, sorafenib resistance is often associated with changes in the tumor microenvironment, and sorafenib-resistant cells were shown to exhibit EMT [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Astragaloside IV, a major effective component of Astragalus membranaceus, increases the secretion of exosomal miR-126-3p and miR-126-5p from human endothelial progenitor cells and promotes angiogenesis ( Xiong et al, 2020 ). Tanshinone IIA, the main pharmacological component of Radix Salvia miltiorrhiza, protects against chronic obstructive pulmonary disease via exosome-shuttled miR-486-5p ( Tian X et al, 2022 ).…”
Section: Regulation Of Exosomes By Traditional Chinese Medicinementioning
confidence: 99%